PENGEMBANGAN SDM MELALUI MANAJEMEN DIRI - Saoqillah, Akhmad (Economic Faculty, Attahiriyah Islamic University, 2016)
Self-management is one step towards success. This means that to achieve something we must begin with self-management. One of them with positive thinking (Positive Thinking). This will facilitate our way to immediately succeed. Positive thinking will take us in the right direction. More recently there was a study that says that a happy plus hard work will lead to success. This means there must be a feeling of happiness within yourself. Human equipped by God incredible strength. The actual power is in him, the force of spiritual, emotional, intellectual and physical. Keywords: self-management, HR development